2005
DOI: 10.1002/ana.20755
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and MTHFR C677T genotype in a population‐based sample

Abstract: ObjectiveMigraine with aura is associated with increased risk of stroke. The MTHFR C677T genotype has been associated with increased risk of migraine in selected clinical samples and with elevated homocysteine, a risk factor for stroke. We assessed the association of the MTHFR C677T variant with migraine and the mediating effect of cardiovascular risk factors and metabolic markers of genotype status.MethodsWe compared adult migraineurs with aura (MA; n = 187), without aura (MO; n = 226), and nonmigraineurs (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
162
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 192 publications
(170 citation statements)
references
References 20 publications
(20 reference statements)
6
162
2
Order By: Relevance
“…Preliminary reports suggest other genetic mutations are somehow involved with increased risk of having the condition of migraine. Recently an endothelial nitric oxide synthase polymorphism, homozygous Asp298, was found to have a 3-fold increased risk for migraine [55], while MTHFR C677T genotype, which is known to be associated with an increase risk for stroke, had a 2-fold increase for migraine [56].…”
Section: Risk Factors In Migraine Headachementioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary reports suggest other genetic mutations are somehow involved with increased risk of having the condition of migraine. Recently an endothelial nitric oxide synthase polymorphism, homozygous Asp298, was found to have a 3-fold increased risk for migraine [55], while MTHFR C677T genotype, which is known to be associated with an increase risk for stroke, had a 2-fold increase for migraine [56].…”
Section: Risk Factors In Migraine Headachementioning
confidence: 99%
“…Research has shown it to be an autosomal dominant disorder involving multiple different mutations of P/Qtype voltage gated calcium channels (for specific information about mechanisms, see Pathophysiology of Migraine section below) [53,54]. Preliminary reports suggest other genetic mutations are somehow involved with increased risk of having the condition of migraine.Recently an endothelial nitric oxide synthase polymorphism, homozygous Asp298, was found to have a 3-fold increased risk for migraine [55], while MTHFR C677T genotype, which is known to be associated with an increase risk for stroke, had a 2-fold increase for migraine [56].Even with all these positive relationships between migraine and genetic factors, the current opinion is that genetics alone cannot explain the presence of the condition, and therefore, migraine is thought of as a multifactorial disorder [57]. Many different non-genetic factors such as stress, psychic tension, depression, and sleep problems have been implicated in increasing the risk of having the condition of migraine headaches [58][59][60][61][62].…”
mentioning
confidence: 99%
“…Migraine risk factors have been investigated in some populations but not in the Estonian population. The common polymorphisms in the MTHFR gene has been found to contribute to genetic predisposition of migraine in several studies conducted in different European populations (Italy [32], Netherlands [33], etc). Prevalence of the MTHFR 677TT genotype in the general population has been estimated at 8 to 12% [34].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the analysis of small families has shown that the structural abnormalities related to sCAD might be familial and follow an autosomal-dominant pattern of inheritance (Grond-Ginsbach et al, 2002;Hausser et al, 2004). This implicates that genetically determined alterations of the extracellular matrix may play a crucial pathogenic role and that candidate genes involved in the regulation of endothelial and vessel wall functions might increase susceptibility to both conditions (Kloss et al, 2006;Pezzini et al, 2002;Scher et al, 2006).…”
Section: How Can Migraine Lead To Ischemic Stroke?mentioning
confidence: 99%